David vs. Goliath or traditional versus modern retail formats: investigating determinant of customer loyalty in emerging markets - Pennano Villanueva, Carla (2017)
The purpose of this paper is to investigate the determinants of both attitudinal and behavioral customer loyalty by decomposing total customer value into the dimensions posited in Sheth’s theory of consumption values: utilitarian, hedonic, social, epistemic and circumstantial dimensions and empirically test this conceptualization in an emerging market grocery retail context. The principal contribution of this document is the analysis and empirical testing of total customer value incorporating four dimensions; utilitarian and hedonic dimensions and to a lesser extent social values have been well studied in consumer behavior literature however no previous study has incorporated four dimensions at the same time. Being able to increase marketing and retail executives’ understanding of these additional aspects of shopping, such as social and epistemic values together with the other two dimensions of consumer purchasing behavior is very relevant especially in a context of highly competitive, largely commoditized retail markets as differentiating factors and potential sources of competitive advantage.